Analisis Faktor yang Mempengaruhi Produktivitas Pemanen Kelapa Sawit : Literature Review - Nurafrillia Ningsih (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The oil palm plantation sector has high economic value as a producer of vegetable oil which is mostly used by the community. In oil palm plantation companies, the direct labor aspect involved in the production process is the oil palm harvesters. This requires increasing the productivity of palm oil harvesters to produce quality fresh fruit bunches at the mill level. This study aims to analyze determining the labor productivity of oil palm harvesters and the factors that influence it as well as the effect of harvest productivity on the quality of oil palm fresh fruit bunches. The method used is literature review. The method used is a narrative method, by reviewing and analyzing research results related to the factors that affect the productivity of oil palm harvesters. The journals used are 5 journals. Based on a review of 5 journals, the results showed that there were several factors that could affect the productivity of oil palm harvesters, namely income (wages/premiums), dependents, experience, age and motivation.Â